2019
DOI: 10.1111/eos.12618
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of alpha‐lipoic acid against apical periodontitis‐induced cardiac injury in rats

Abstract: This study was designed to assess the possible protective effect of alpha‐lipoic acid (ALA) on apical periodontitis (AP)‐induced cardiac injury. Wistar albino rats were randomized into four groups: control; ALA; AP; and ALA + AP. Rats of the control and ALA groups were not endodontically treated, but saline and ALA (100 mg kg−1) were administered. In rats of the AP and ALA + AP groups, the pulp chambers of mandibular first molar teeth were exposed and left open for 30 d to induce AP. Saline and ALA (100 mg kg−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…According to literature data, there have been no studies that examined the pathohistological changes of the heart under the influence of AP in spontaneously hypertensive conditions; therefore, it could only be compared with the results of studies that investigated the effect of AP on the heart in normotensive conditions. The results of this study partially coincide with the study investigated by Sehirli et al (2019), which showed that AP in normotensive conditions caused oedema, regions of myocardial congestion and the influx of inflammatory cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…According to literature data, there have been no studies that examined the pathohistological changes of the heart under the influence of AP in spontaneously hypertensive conditions; therefore, it could only be compared with the results of studies that investigated the effect of AP on the heart in normotensive conditions. The results of this study partially coincide with the study investigated by Sehirli et al (2019), which showed that AP in normotensive conditions caused oedema, regions of myocardial congestion and the influx of inflammatory cells.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the components of the antioxidant defence system, myocardial SOD activity was lower in SHR + AP and AP groups compared to their control groups, whilst the level of CAT and GSH was similar between groups. The experimental study of Sehirli et al (2019) which dealt with assessing the possible protective effect of alpha‐lipoic acid on AP induced cardiac injury, showed that serum SOD activities were decreased in the AP group compared with the apically healthy control group, as in the present study with myocardial SOD activity. These results suggest the importance of deficiency of antioxidant enzymes in cardiac damage that has developed as a result of AP.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations